Iban Sebuyau Youth Slang : Radial Network Category Framework Analysis = Slanga Remaja Iban Sebuyau : Analisis Kerangka Kategori Jaringan Radial - Clinton, Ringit; Hamidah, Abdul Wahab (Penerbit UTM Press, 2020)
Slang is a free-grammatical rule of language phenomenon that exhibits the invention of vocabulary in a community groups in order to strengthen social identity. Overall, there are 15 data of Iban Sebuyau teenagers slang which has been acquired and separated into noun categories (eight data) and verbs (seven data). This study will analyze seven types of words of Iban Sebuyau teenagers’ slang in Sarawak via the verb category. Besides, the slang of Iban Sebuyau teenagers’ data will be examined based on the Radial Network Category Framework as suggested by Lakoff (1987). Accordingly, this study applied qualitative methods to obtain field sampling based on 10 teenagers in Sebuyau which has been selected based on their comprehension on the slang. As a result, the findings shows that there are in total of 7 data of Iban Sebuyau teenagers slang has been obtained in verb categories such as merueh, ngaga’ peta, ngangat nyawa, belagu, nunjuk langit, melabur, and fogging. Overall, the Radial Network Category Framework approach able to describe the extensive meaning of Iban Sebuyau teenagers slang.